2017
DOI: 10.1007/s00464-017-5789-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of visual–spatial ability on laparoscopic camera navigation training

Abstract: In the present study, all trainees improved LCN performance during the training. VSA seems to have impact on LCN performance and training progress particularly for complex LCN tasks. The relation of VSA and LCN performance was stronger for less experienced participants and in the beginning of the learning phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The influence of gender on surgical skill acquisition is not clear yet [ 30 ]. Although studies of Schueneman et al [ 31 ] and Madan et al [ 32 ] found some differences between males and females in surgical skill acquisition [ 33 ], the findings of Kolozsvari et al [ 34 ], Grantcharov et al [ 35 ], Nickel et al [ 36 ], and Kowaleski et al [ 37 ] support the results of our study that no correlation between operative performance and gender of participants could be found.…”
Section: Discussionsupporting
confidence: 69%
“…The influence of gender on surgical skill acquisition is not clear yet [ 30 ]. Although studies of Schueneman et al [ 31 ] and Madan et al [ 32 ] found some differences between males and females in surgical skill acquisition [ 33 ], the findings of Kolozsvari et al [ 34 ], Grantcharov et al [ 35 ], Nickel et al [ 36 ], and Kowaleski et al [ 37 ] support the results of our study that no correlation between operative performance and gender of participants could be found.…”
Section: Discussionsupporting
confidence: 69%
“…These skills contribute to the representation of the human body, allowing the understanding of relation between structures and three-dimensionality (Guillot et al, 2007;Langlois et al, 2015;Langlois et al, 2017). Moreover, the relevance of spatial abilities in anatomy education has shown an impact in different medical fields such as medical imaging (van der Gijp et al, 2014) or laparoscopic surgery (Roch et al, 2018).…”
Section: Spatial Abilities In the Context Of Anatomy Educationmentioning
confidence: 99%
“…Indeed, spatial abilities serve as a predictor of the learning time, performance and knowledge acquisition in anatomy (Guillot et al, 2007;Berney et al, 2015;Langlois et al, 2017). Likewise, several studies drew strong correlations between these skills and the easiness to incorporate new information or techniques in the surgical field (Wanzel et al, 2003;Stefanidis et al, 2006;Buckley et al, 2014;Langlois et al, 2015), namely laparoscopic surgery (Stefanidis et al, 2006;Kramp et al, 2016;Roch et al, 2018), and radiology (van der Gijp et al, 2014;Birchall, 2015).…”
Section: Students' Spatial Abilities Performance Improvementmentioning
confidence: 99%
“…The analysis of the operation time as a surrogate parameter may seem easier at first glance. The comparison of time, however, can only be an adequate surrogate parameter for the assessment of camera navigation quality in standardized simulation scenarios [3,8,14,19]. It is not as qualified for an intraoperative assessment, in which the procedure time is also influenced by the main surgeon's operative experience and multiple patient-specific factors [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of minimally invasive surgery for depth perception, reduction of tactile feedback, and the fulcrum effect (the optical inversion of the movements on the screen) do not apply to the main surgeon only but also to the (camera) assistant [1,2]. Therefore, handling the laparoscope is a complex psychomotor task that requires an appropriate visual-spatial ability, hand-eye coordination, and anticipatory knowledge of the surgical procedure [1,3,4]. Poor camera navigation (i.e., errors in horizon, instrument collisions, smudges, and failure to achieve a stable view) can compromise the flow of the operation resulting in increased frustration of operating surgeons and prolongation of operating time and therefore may compromise patient safety [5,6].…”
Section: Introductionmentioning
confidence: 99%